Cellulose Impact on Bioplastic Performance: A Study on Mechanical Strength, Physical Properties, and Degradation of Water Hyacinth and Kepok Banana Peel-derived Materials - Faiza Armalia Putri; Aditya Rianjanu; Wahyu Solafide Sipahutar (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Plastics, primarily made of synthetic polymers, are difficult to degrade by microbes, resulting in waste management challenges. Bioplastics are a viable alternative to conventional plastics' environmental problems. They are crucial for circular economy transformation and sustainability goals. To address this issue, researchers investigated the formation of bioplastics from kepok banana peels (Musa acuminata) and water hyacinth (Eichhornia crassipes). This study will investigate the mechanical properties, degradation rate, water absorption, and functional groups of these bioplastics. Various cellulose concentrations (0%, 4%, 8%, 12%, and 16%) are used throughout the manufacture. The results show that cellulose content has a substantial influence on the mechanical characteristics, degradation rate, and water absorption of bioplastics. Bioplastics having 12% cellulose had the best mechanical properties with a tensile strength of 2.551 MPa. Bioplastics containing 4% cellulose, on the other hand, degrade the fastest, losing 63.181% of their mass. This high degradation rate corresponds to the maximum amount of water absorption, which reaches 54.93%. Furthermore, the FTIR study shows that no novel functional groups were discovered in the bioplastics. In conclusion, using kepok banana peel starch and water hyacinth to generate bioplastics shows potential as a solution to the problems that traditional plastics face. This research shows that changing the cellulose content in bioplastics can cause changes in mechanical qualities, breakdown rate, and water absorption. More studies in this area might pave the way for more ecologically friendly and sustainable alternatives to existing plastics. Keywords: Bioplastic, Banana peel starch, Water hyacinth, Cellulose, FTIR